Grammatical Words Combination for Children 3-4 Years - Erna Megawati; Ninuk Lustyantie; Zainal Rafli (Universitas Indraprasta PGRI, 2019)
Abstract: The purpose of the research is to analyze grammatical of word combination in 3004 years old children and its relation to gender. The sample consists of 4 children which are 2 girls and 2 boys. The method of the research is descriptive qualitative. The source of data is taken from utterances uttered by samples. The technique of data collection is tapping and noting. Data then analyzed using theory of Pivot Grammar by Brainne. The results show if samples produced 3 – 6 variations of grammatical of word combination and 2 variation of pivot grammar position. The findings of this research show if girls produced more variation than boys but less in number of pivot grammar’s position.